2009
DOI: 10.3892/ijmm_00000162
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellin and des-cerebellin exert ACTH-like effects on corticosterone secretion and the intracellular signaling pathway gene expression in cultured rat adrenocortical cells - DNA microarray and QPCR studies

Abstract: Abstract. Precerebellins (Cbln) belong to the C1q/TNF superfamily of secreted proteins which have diverse functions. They are abundantly expressed in the cerebellum, however, three of them are also expressed in the rat adrenal gland. All members of the Cbln family form homomeric and heteromeric complexes with each other in vitro and it was suggested that such complexes play a crucial role in normal development of the cerebellum. The aim of our study was to investigate whether Cbln1-derived peptides, cerebellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Rat primary adrenocortical cell culture. Method of culturing rat adrenocortical cells was described earlier [34][35][36]. Briefly, adrenals were obtained from 40, 20-22-day-old male rats.…”
Section: In Vivo Experiments Effects Of Acth On Sirtuin Genes Expresmentioning
confidence: 99%
“…Rat primary adrenocortical cell culture. Method of culturing rat adrenocortical cells was described earlier [34][35][36]. Briefly, adrenals were obtained from 40, 20-22-day-old male rats.…”
Section: In Vivo Experiments Effects Of Acth On Sirtuin Genes Expresmentioning
confidence: 99%
“…Investigations about the effects of cerebellin on circulation are very limited. Rucinski et al demonstrated that cerebellin-derived peptides have adrenocorticotropic hormone (ACTH)-like effects on corticosterone output and proliferative activity of cultured rat adrenocortical cells [28]. Previous studies showed that cerebellin is a potent stimulator of direct norepinephrine release by rat adrenal medulla and enhances adrenocortical steroid secretion.…”
Section: Discussionmentioning
confidence: 99%